Philippines Economic Update, June 2022 : Strengthening the Digital Economy to Boost Domestic Recovery - World Bank (Washington, DC, 2022)
Digitalization represents a key driver for long-term economic growth. While the use of digital technology has accelerated during the pandemic, the Philippines has not fully leveraged its expected benefits. There has been progress in expanding digital connectivity, but challenges remain. The explosive digitalization during the pandemic requires policies to keep up with the pace of development of the digital economy.